2014
DOI: 10.1021/nl500212s
|View full text |Cite
|
Sign up to set email alerts
|

Band Offset and Negative Compressibility in Graphene-MoS2 Heterostructures

Abstract: We use electron transport to characterize monolayer graphene-multilayer MoS2 heterostructures. Our samples show ambipolar characteristics and conductivity saturation on the electron branch that signals the onset of MoS2 conduction band population. Surprisingly, the carrier density in graphene decreases with gate bias once MoS2 is populated, demonstrating negative compressibility in MoS2. We are able to interpret our measurements quantitatively by accounting for disorder and using the random phase approximation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
144
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(154 citation statements)
references
References 50 publications
9
144
0
Order By: Relevance
“…Third, free carriers in low-dimensional systems form a low-energy acoustic plasmon which can dynamically couple with quasiparticles. These effects result in an enhanced many-body renormalization of quasiparticles energy, as shown from previous theoretical GW calculations in both semiconducting carbon nanotubes [21,22] and 2D transition metal dichalcogenides (TMDs) [23], and from experimental measurements [24][25][26][27]. More recently, beyond the nonlinear quasiparticle band gap renormalization of several hundred meV, the optical gap of monolayer TMDs was predicted to stay nearly constant due to a cancellation with the renormalization of exciton binding energy [28].…”
Section: Introductionmentioning
confidence: 78%
“…Third, free carriers in low-dimensional systems form a low-energy acoustic plasmon which can dynamically couple with quasiparticles. These effects result in an enhanced many-body renormalization of quasiparticles energy, as shown from previous theoretical GW calculations in both semiconducting carbon nanotubes [21,22] and 2D transition metal dichalcogenides (TMDs) [23], and from experimental measurements [24][25][26][27]. More recently, beyond the nonlinear quasiparticle band gap renormalization of several hundred meV, the optical gap of monolayer TMDs was predicted to stay nearly constant due to a cancellation with the renormalization of exciton binding energy [28].…”
Section: Introductionmentioning
confidence: 78%
“…At the hetero-contact structure, the positive back-gate bias not only electro-statically dopes MoS 2 , but also could move the Fermi-level in Ti doped n-type graphene [18][19][20][21] further up beyond the Ti/MoS 2 pinning level, thus enhance the electron injection from metal into the conduction band of MoS 2 leading to a lower contact resistance. The key difference from previous devices is that the back-gate can modulate not only the Fermi-level of the channel but also the contact (graphene) as shown in the inset of Figure 3(b) [19]. The total carrier density summed over graphene and MoS 2 hetero-contact exceeds the single MoS 2 /metal contact, where the monolayer graphene can be seemed as a "charge pumping" layer.…”
Section: Resultsmentioning
confidence: 99%
“…This section is devoted to studies on the close relationship between these two materials. As graphene and SLMoS 2 have complementary physical properties, it is natural to combine graphene and SLMoS 2 in specific ways to create heterostructures that mitigate any negative properties [25,26,[187][188][189][190][191][192][193][194][195][196][197].…”
Section: Graphene/mos 2 Heterostructurementioning
confidence: 99%
“…These mechanical properties have been used to protect MoS 2 films from radiation damage [26]. Recently, Larentis et al measured the electron transport in graphene/MoS 2 heterostructures and observed a negative compressibility in the MoS 2 component [191]. This surprising phenomenon could be explained based on the interplay between the Dirac and parabolic bands for graphene and MoS 2 , respectively.…”
Section: Graphene/mos 2 Heterostructurementioning
confidence: 99%